Experiencing archaeology : a manual of classroom activities, demonstrations, and minilabs for introductory archaeology - Homsey-Messer, Lara
Today, many general-education archaeology courses are large, lecture-style class formats that present a challenge to providing students, particularly non-majors, with opportunities to learn experientially. This laboratory-style manual compiles a wide variety of uniquely designed, hands-on classroom activities to acquaint advanced high school and introductory college students to the field of archaeology. Ranging in length from five to thirty minutes, activities created by archaeologists are designed to break up traditional classroom lectures, engage students of all learning styles, and easily integrate into large classes and/or short class periods that do not easily accommodate traditional laboratory work.